Para uma epistemologia da errância: erro, hiância e ciência em Michel Pêcheux - Almeida, João Flávio de (Universidade Federal de São Carlos, 2018)
Under the aegis of French Discourse Analysis, more specifically in Michel Pêcheux, the objective of this thesis is to establish a basis for a errancy (wander) epistemology: a theory of knowledge based on non-logically-stabilized that may substantiate the listening, production and circulation of other knowledge, and then produce changes in sense and subject. Our proposal is placed in the touching areas of knowledge semantics, philosophy and sociology, and for this reason will be limited to only analysing the production and circulation of “scientific” knowledge in the contemporary world. To this end we will consider the senses that oscillate between errancy and error, and from them suggest a theoretical itinerary that casts light onto the sedentarisation (stabilisation, decrease, administration and profit) of the signification from the ideological-political implementation of the concepts of mistake and success regarded by the discourse called “scientific”. We will go through two of the author’s main works: “Language, Semantics, and Ideology” (2009), and "Discourse: Structure or Event?" (2008), following the tenuous line of errancy that passes through these works and through discussions concerning “mistake” in language, the gaps that divide and cause changes in the parts that make up the linguistic base and the processes of discourse, and about the logical-rhetorical stabilisation of the senses through the scientific method and the computational axiom of the techno science.
Keywords: Epistemologia; Ciência; Erro; Errância; Michel Pêcheux; Epistemology; Science; Error; Wandering; Michel Pêcheux; CIENCIAS HUMANAS::FILOSOFIA::EPISTEMOLOGIA; LINGUISTICA, LETRAS E ARTES::LINGUISTICA